A disposable biosensor for noninvasive diabetic diagnosis rest on the Au/TiO2 nano-composite intensified electrochemiluminescence. (1st September 2016) - Yu, Liyan; Wei, Xiuhua; Fang, Chen; Tu, Yifeng
Abstract: In this work, a novel enzymatic electrochemiluminescent (ECL) biosensor based on the sensitization from Au/TiO2 nano-composite was prepared for noninvasive glucose detection. The Au/TiO2 nano-composite was deposited on the surface of indium tin oxide glass by Nafion, which significantly enhanced the ECL of luminol after calcination, and a sensitive response toward hydrogen peroxide was obtained. Glucose oxidase was cross-linked with bovine serum albumin by glutaraldehyde and immobilized on electrode surface. It worked as the sensing matrix and catalyzed the oxidation of glucose to produce H2 O2, thus an enhanced ECL emission was resulted. Under the optimized conditions, this biosensor showed good stability, selectivity, sensitivity and simplicity. It has a wide linear range for the detection of glucose from 7.0 μM to 100 μM with a detection limit of 0.22 μM. The sensor has been successfully applied to detect glucose in diluted human serums and saliva samples. Therefore, this sensor could be regarded as a simple, practical and disposable device in a noninvasive manner of routine glucose monitoring for diabetics.